2018
DOI: 10.3892/mmr.2018.9712
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms shaping the role of ERK1/2 in cellular sene scence (Review)

Abstract: Senescence is a result of cellular stress and is a potential mechanism for regulating cancer. As a member of the mitogen-activated protein kinase family, ERK1/2 (extracellular signal-regulated protein kinase) has an important role in delivering extracellular signals to the nucleus, and these signals regulate the cell cycle, cell proliferation and cell development. Previous studies demonstrated that ERK1/2 is closely associated with cell aging; however other previous studies suggested that ERK1/2 exerts an oppo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
65
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(66 citation statements)
references
References 134 publications
1
65
0
Order By: Relevance
“…The nuclear regulation of ERK signalling with other phosphorylated proteins in the cell is very important to regulate the normal function of cells such as the cell cycle, cell proliferation and cell development. [ 49,50 ] Also, researchers expressed there was a possibility that generated ROS and RNS/NO in tumour cells regulate MMP9 expression and/or activation. [ 51–53 ] Flavonoids/flavones are direct scavengers of ROS and RNS.…”
Section: Discussionmentioning
confidence: 99%
“…The nuclear regulation of ERK signalling with other phosphorylated proteins in the cell is very important to regulate the normal function of cells such as the cell cycle, cell proliferation and cell development. [ 49,50 ] Also, researchers expressed there was a possibility that generated ROS and RNS/NO in tumour cells regulate MMP9 expression and/or activation. [ 51–53 ] Flavonoids/flavones are direct scavengers of ROS and RNS.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, ERK1/2 is a major member of Mitogen-activated protein kinases (MAPKs) family, which are ubiquitous eukaryotic signal transduction enzymes that stimulate the pathways related to intracellular gene expression and acting kinases. Therefore, ERK1/2 mediates extracellular signals to the nucleus for the regulation of cell cycle and cell proliferation 40,41 . Increasing evidence shows that SGK1 is a member of the CALMP-dependent protein kinase A, cGMP-dependent kinase G, and phospholipid-dependent protein kinase C (AGC) family of serine or threonine protein kinases and serves as a downstream regulator in the PI3K pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Erks are also known to activate many transcription factors (e.g. c-myc, c-Fos, AP-1, and Elk1) responsible for regulation of various target genes [35]. It has been found that Ang II stimulates Erk1/2 activation and Nox4-derived ROS production in glomerular mesangial cells [36].…”
Section: Plos Onementioning
confidence: 99%